Information Needs in the 21st Century: Will ERIC Be Ready? - Rudner, Lawrence M. (Education Policy Analysis Archives, 2000)
Ubiquitous for 35 years, the Educational Resources Information Center (ERIC) is known for its database and recently for its range of web-based information services. I contend that federal policy with regard to ERIC must change and that ERIC will need massive restructuring in order to continue to meet the information needs of the education community. Five arguments are presented and justified: 1) ERIC is the most widely known and used educational resource of the US Department of Education, 2) senior OERI and Department of Education officials have consistently undervalued, neglected, and underfunded the project, 3) ERICs success is due largely to information analysis and dissemination activities beyond ERICs contracted scope, 4) information needs have changed dramatically in the past few years and ERIC cannot keep up with the demands given its current resources, and 5) the ERIC database itself needs to be examined and probably redesigned.